Mechanical and Structural Characterization of Resole Resin Composites Reinforced with Sabai Grass-Derived Cellulose Fibers - Puri, Aabha; Adhikari, Rameshwar; Pandit, Rajesh (Journal of Nepal Chemical Society, 2024)
Cellulose fibers were extracted from Sabai grass (Eulaliopsis binata) using mechanical and chemical treatments. The grass was ground to 250 µm powder and bleached with hydrogen peroxide and acetic acid. The bleached fibers were treated with 6% sodium hydroxide solution and incorporated into resole resin at various weight percentages to prepare the composites. The prepared samples were characterized by X-ray Diffraction (XRD), Fourier Transform Infra-Red (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), and compressive strength tests. The XRD and FTIR showed a nanometric crystallite size of 3.84 nm and effective removal of non-cellulosic compounds, respectively, leading to a compressive strength increase from 15.60 MPa to 25.26 MPa at 3 wt.-% cellulose fiber. The compressive strength improved up to 3 wt.-% cellulose fiber, which however declined upon adding more filler. SEM revealed modified surface morphology in the composites with cellulose fibers.